REKONSTRUKSI KONSEP KETATANEGARAAN ISLAM TERHADAP SISTEM PEMERINTAHAN DEMOKRASI PRESIDENSIAL DI INDONESIA - Fauzan Zakir (Ensiklopedia of Journal, 2019)
The basic doctrine of Islam is not contrary to democracy and modernization. For example, the doctrine of Islam is advanced enough to support democracy that is parallel to the ideals of modernization. Many Islamic scholars have re-examined the roots and treasures of Islam. Convincingly the Islamic scholars concluded that Islam and democracy were not only compatible; on the contrary, both associations are unavoidable, because the Islamic political system is based on deliberation (syura). A number of Islamic intellectuals and scholars have struggled to find common ground between the Islamic world and the Western world towards a better mutual understanding of the relationship between Islam and democracy. Because, most existing discourse seems too fixated on labels that are used stereotypically by a number of circles. Islam as stated in the hadith: "The state is a protection for those who have no protector". Whatever state the form of the system, insofar as it can facilitate, guarantee, protect the implementation of religion, it can be legally recognized according to syara '. Especially in Indonesia, although it is not a textual basis, Islam is a sprit in its formation. Islam justifies the existence of the state with any system, as long as it is in harmony with or the same as the goal of sharia, namely being able to maintain religion, property, soul, mind, and descent. With this statement, Indonesia is one of Darul Islam (Islamic Regions) not Daulah Islamiyah (Islamic State), therefore, the presidential government system may be applied even though it has a Muslim majority.